2019
DOI: 10.1007/s11069-019-03655-8
|View full text |Cite
|
Sign up to set email alerts
|

A large wet snow avalanche cycle in West Greenland quantified using remote sensing and in situ observations

Abstract: On 11 April 2016 we observed high slushflow and wet snow avalanche activity at the environmental monitoring station Kobbefjord in W-Greenland. Snow avalanches released as a result of snow wetting induced by rain-on-snow in combination with a strong rise in air temperature. We exploit high-resolution satellite imagery covering pre-and post-event conditions for avalanche quantification and show that nearly 800 avalanches were triggered during this cycle. The nature of this extraordinary event is put into a longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
2
34
1
Order By: Relevance
“…As manual avalanche mapping is time consuming, a reliable automation of this process would make the mapping data quickly available for further application. Therefore, different attempts have been made to automatically detect avalanches mainly on the two satellite platforms S1 (Vickers et al, 2016;Wesselink et al, 2017;Abermann et al, 2019), and Radarsat-2 (Hamar et al, 2016;Wesselink et al, 2017). The general workflow in these papers is quite similar to ours.…”
Section: Automated Avalanche Detectionmentioning
confidence: 87%
See 1 more Smart Citation
“…As manual avalanche mapping is time consuming, a reliable automation of this process would make the mapping data quickly available for further application. Therefore, different attempts have been made to automatically detect avalanches mainly on the two satellite platforms S1 (Vickers et al, 2016;Wesselink et al, 2017;Abermann et al, 2019), and Radarsat-2 (Hamar et al, 2016;Wesselink et al, 2017). The general workflow in these papers is quite similar to ours.…”
Section: Automated Avalanche Detectionmentioning
confidence: 87%
“…They concluded that medium to large avalanche events could be mapped using very high resolution radar satellites but with the drawbacks of limited availability and high costs. Nevertheless, for freely available but medium-resolution Sentinel-1 radar images few but promising avalanche mapping studies exist (Vickers et al, 2016;Eckerstorfer et al, 2017;Wesselink et al, 2017;Abermann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with pre-event satellite data, forest destruction can be mapped with the same methodology as for the avalanches. Such information is crucial for a fast and target-oriented management of protected forests (Bebi et al, 2009) and the initiation of necessary development of protection infrastructure (Miklau et al, 2014). This is particularly useful in remote regions that are hardly accessible in winter.…”
Section: Potential Improvements and Follow Up Analysismentioning
confidence: 99%
“…Radar satellites have the advantage of acquiring data despite clouds and without daylight. Therefore, radar data have also been applied to generate avalanche maps (Eckerstorfer and Malnes, 2015;Vickers et al, 2016;Eckerstorfer et al, 2017;Wesselink et al, 2017) and were recently also used for a large avalanche period in Greenland (Abermann et al, 2019). Due to the coarser spatial resolution (3-30 m) and limitations by the observation geometries (radar shadow and layover), considerable parts of mountain regions cannot be covered.…”
Section: Introductionmentioning
confidence: 99%
“…GIS is a powerful tool for the construction of terrain’s geographical database to support building accurate prediction and decision-making models with high precision for terrain visualization 50 54 . Also, RS contributes to data collection through remotely sensing the inaccessible mountainous areas, which are a real asset in replacing costly and slow ground data collection systems without disturbing the snow cover 2 , 29 , 55 , 56 .…”
Section: Introductionmentioning
confidence: 99%